(untitled) (Boletim de Conjuntura (BOCA), 2025)
The participation of health professionals in Multidisciplinary Health Residency Programs (PRMSs) has grown significantly in several regions of Brazil in recent years. With this growth, there has been a growing appreciation and redefinition of the roles of preceptors and tutors, who now occupy a central position in in-service training. The present study aimed to identify and discuss the representational elements constructed and shared by psychology professionals who act as tutors and/or preceptors in the context of training offered and developed in PRMSs, with regard to professional training and qualification. This is a qualitative study, conducted within an exploratory and descriptive research design with cross-sectional data, grounded in the Theory of Social Representations. Seven psychologists who had been working as tutors and preceptors in the Multiprofessional Health Residency (RMS) for at least two years participated in the PRMS of a public hospital located in Goiânia, in the state of Goiás. The data was collected in October 2024 through a focus group, with the aim of deepening the perceptions and representations developed by the participants, and a typical questionnaire that included the following question: “What comes to mind when you think of RMS? ” The data was processed using Requalify.ai software and interpreted using thematic-categorical content analysis. The analysis resulted in six categories: Contradictory Feelings about the Experience; Learning and Opportunities in the Training Process; Challenges and Workload in the Residency; Need for Specific Training; and Importance of Self-Care and Qualified Listening. From this overview, it was observed that the social representations constructed by the participants reflected a training experience in the RMS marked by challenges, responsibilities, frustrations, and devaluation, but also permeated by opportunities for learning, professional development, and strengthening collaborative practices in teamwork. It was concluded that the duties of preceptors and tutors lack a precise definition, which highlights the importance of recognizing these roles and providing specialized professional training.